Close To Death : Hawthorne and Horowitz # 5 Book 5 : Detective Daniel Hawthorne. - Horowitz, Anthony, 1955- (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2024)
"Riverside Close is a picture-perfect community. The six exclusive and attractive houses are tucked far away from the noise and grime of city life, allowing the residents to enjoy beautiful gardens, pleasant birdsong, and tranquility from behind the security of a locked gate. It is the perfect idyll, until the Kentworthy family arrives, with their four giant, gas-guzzling cars, gaggle of shrieking children, and plans for a garish swimming pool in the backyard. Obvious outsiders, the Kentworthys do not belong in Riverside Close, and quickly offend every last one of the neighbors. When Giles Kentworthy is found dead on his own doorstep, a crossbow bolt sticking out of his chest, Detective Hawthorne is the only investigator they can call to solve the case. Because how do you solve a murder when everyone is a suspect?"--.
new book 2024 spring.
Keywords: Horowitz, Anthony, -- 1955- -- Fiction; Hawthorne, Daniel -- (Fictitious character) -- Fiction; Murder -- Fiction; Murder -- Investigation -- Fiction; Private investigators -- Fiction; Authors -- Fiction; Neighbors -- Fiction; Gated communities -- Fiction; England -- Fiction; Detective and mystery fiction; Novels; Thriller fiction; Detective fiction; Mystery fiction